Plan Estratégico para la Empresa “El Palteñito” de la Ciudad de Catacocha, periodo 2022-2027 - Fajardo Collaguazo, Santos Fabricio (2023)
Palteñito is a company from the city of Catacocha, in the Paltas cantón of the province of Loja, in the sector of production and sale of products, dedicated to the processing of grains that has been present in the market since 2018. The company produces ground coffee, corn flour, peanut paste, products that are marketed locally, and also the sale of orders at the level of the province of Loja and the rest of the country. The general objective is to develop a strategic plan for the company el Palteñito, to implement new strategies and achieve greater competitiveness; As specific objectives we have: Determine a situational diagnosis of the company, using the PESTEL analysis (external), Perform a SWOT analysis, Identify the strategic objectives through the FO-FA-DO-DA matrix, Design a proposal for a strategic plan. For this project a descriptive research was carried out, using the Analytical-Descriptive method, and the Deductive Method; using the following techniques: surveys, interviews and direct observation; in which the number of surveys of 248 for clients and 5 for workers and the interview with the manager of the company was estimated. Among the most relevant results is the use of the matrices to be able to establish, the objective lines, to propose the strategies to be implemented in the company the Palteñito, for which we obtained the results from criteria taken, to improve competitiveness and increase the volume of sales, of which 4 strategies to be implemented are established, with their respective specifications and deadlines for compliance, with their respective budget. Therefore, in this conclusion we can emphasize some important aspects of the research of the Palteñito company, to be able to know the internal part and the external aspects that influence the operation of the company, for which the information given in the survey and interview that helped to formulate the weaknesses and strengths was taken, opportunities and threats, thus giving us the result of 4 strategies within the framework of competitiveness and promotion. Key words: Strategic planning, company, innovative projects.